Impact of COVID-19 Pandemic on Consumer Behavior towards the Intention to Use E-Wallet in Malaysia - Edeh, Friday Ogbu; Aryani, Dwi Nita; Subramaniam, Tanuja A/P; Kee, Daisy Mui Hung; Samarth, Tejas; Nair, Rajesh Kumar; Kannappan, Thirumagal A/P; Tan, Yee Shan; Teh, Yi Ching (AIBPM Publisher, 2021)
The technology-driven era has encouraged Malaysians to use e-Wallet rather than paper money in their daily transactions. Numerous e-Wallet applications have been developed, such asÂ GrabPay, Touch 'n Go eWallet, and Boost. Erstwhile, Malaysians perceived that using e-Wallets is troublesome and worthless. However, the COVID-19 outbreak has reframed the buyers' perceptions otherwise. This study investigates the impact of Covid-19 on consumer behavior towards the intention to use e-Wallet in Malaysia. A sample of 100 Malaysians has voluntarily participated in this survey. Data were assembled through an electronic survey questionnaire. Contrary to popular belief, the findings depicted that the behavioral intention to use e-Wallets among Malaysians had further accelerated due to the convenience perceptions, facilitating conditions, and perceived safety.Â